Pengaruh kualitas ransum berbeda terhadap bobot relatif kuning telur dan profil leukosit Ayam Kedu pasca tetas (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The research aimed to evaluate the effect of different quality of diet on yolk relative weight and leukocytes profile of post-hatch Kedu chicks. The research used 105 birds of day-old Kedu chicks, which were devided into T0 = fasted for three days post-hatch continued feed farmer ration; T1 = farmer’s ration; T2 = improved rations. Improved ration contains higher protein and energy than the farmer’s ration. Completely randomized design (CRD) with split in time was assigned to the present study. The main plot was age of chicks and the subplot was dietary treatment. Parameters measured were yolk relative weight, leukocyte and differential leukocyte profiles. The results showed that there was no significant effect on either interaction (P>0.05) between age and dietary nutriens quality or the main plot on yolk relative weight, leukocytes and differential leukocyte profiles in Kedu chicks 6 days post-hatch. However, yolk relative weight was affected significantly by the sublot, and other parameters were the same. Conclusion of the research was that the yolk relative weight, leukocyte and differential leukocyte profiles remained stable in 6 days post-hatch Kedu chicks despite being given ration with the different nutrients quality, including fasted-group’s chicks three days after hatch. Keywords: post-hatch Kedu chicks, egg yolks, leukocyte profiles, improved ration